(untitled) (Colloquia Comparativa Litterarum, 2025)
The European topos in the new Macedonian novel is accepted as a home. Young Macedonian authors consider Europe their home. The fact that they live outside the European Union, or outside the European West, which has for a long time been considered the implicit cultural centre of the world, does not make them less European. Originally born in Macedonia, a cultural centre of the distant past that used to consider Western Europe a periphery, writers such as Goce Smilevski and Olivera Kjorveziroska materialize in their works the ‘Western European topos’ in a seemingly sidelong, but none the less essential manner. They draw attention to the dark side of Western culture and the suppressed content that official historiography tends to conceal. They remind us that Europe’s spiritual being knows no boundaries and that literature transcends institutional, conceptual, and ethical frontiers. Liberated from European stigma (fallacious moral, repressed memory, colonial traumas), these Macedonian authors reveal certain parts of the European Shadow (the collective unconscious, the historical archives full of shameful bits). No civilization is without its dark facets. That is the law of Light. That is how Europe is, composed of West and East, but also of North and South. It is liminal and intercultural. In its process of assimilating, it becomes assimilated. The interpretation focuses on novels by Goce Smilevski (Razgovor so Spinoza / Conversation with Spinoza, 2002; Sestrata na Sigmund Frojd / Sigmund Freud’s Sister, 2007/2010, Vrakanjetо na zborovite / The Return of the Words, 2015) and by Olivera Kjorveziroska (Zakluchenoto telo na Lu / Lou’s Locked Body, 2005).